International spillovers in a world of technology clubs - Roman Stöllinger (FIW - Research Centre International Economics, 2013)
Technology is a key element for long-term growth and economic development. Given the stark concentration of innovation activities in a few countries most countries have to rely on the international diffusion of newly developed technologies. Some countries may fail to successfully perform the task of technology adaption leading to a tripartite segmentation of countries into an innovation club, an imitation club whose members are capable of absorbing technologies developed by the former and a stagnation group that lack the capability to absorb foreign technologies. We test the role of the technology gap for growth as suggested by the technology club hypothesis in a threshold regression framework using human capital as the threshold variable. Using this approach, which is related to Benhabib-Spiegel type growth regressions, we are able to identify two distinct thresholds giving rise to three country groupings. As suggested by the theory of technology clubs we find the strongest effects from the catch-up term on economic growth for the intermediate group (imitation club).
Keywords: O47; O41; I25; O33; 330; technology clubs; threshold regressions; technology spillovers; Schumpeterian growth model; human capital